.NET Development for the web; Using Microsoft Office SharePoint Server 2007 and ASP.NET - Jacobsson, Oskar (My University, 2009)
For a company or organisation, it has become very important to 'exist on the web', that is to provide a webpage where information, goods available for purchase and services etc. are available for the customers. As a natural consequence of an increased interest for the Internet and its fast growth, software developing companies sometimes needs to adapt their solutions for the web. In this thesis, several methods and solutions for web development within .NET are proposed. The solutions are in most cases related to Microsoft Office Excel where the possibilities and limitations for web publishing of workbooks are investigated. The main focus is on Microsoft Office SharePoint Server 2007 and ASP.NET solutions. In SharePoint, several solutions are proposed for dealing with limitations with Excel Services and Excel Web Access when publishing workbooks. SharePoint is also examined further for solutions for database handling and COM automation. An application that publish Excel workbooks on the web is developed with ASP.NET, and presenting ways of displaying and interacting with a workbook published to a server. We also look at a way of presenting data visually on the web, using Microsoft Chart Controls for .NET Framework 3.5 which can present data in chart format. Office Open XML are proposed as an alternative for COM automation when publishing Excel workbooks on the web.
Keywords: Programvaruteknik; Software Engineering